The enzyme biorefinery platform for advanced biofuels production. (September 2019) - Singh, Anusuiya; Rodríguez Jasso, Rosa M.; Gonzalez-Gloria, Karla D.; Rosales, Miriam; Belmares Cerda, Ruth; Aguilar, Cristóbal N.; Singhania, Reeta Rani; Ruiz, Héctor A.
Abstract: The increasing demand for energy has resulted in the exploitation of fossil fuels, which led to its depletion; therefore, this has focused our attention on the development of alternative energy sources in the advanced biofuels production. Lignocellulosic biomass is available abundantly on this earth, which is renewable and a better choice for bioethanol production as well as in terms of biorefinery concept. For bioethanol production using enzyme and the biochemical platform is considered to be a better approach as it is eco-friendly and more feasible. Around 15% to 20% of the total cost of biofuel production is of the enzyme; therefore, it has become today's requirement to produce enzyme and develop other methods or processes to enhance enzyme production. This review discusses the development in fermentation and culturing technique to improve enzyme production and the pretreated solid after of hydrothermal process as the inducer in the enzyme production for advances in biofuels. Highlights: The concept of biorefinery and their classification Pretreatment and enzymes role in the second-generation biorefinery Hydrothermal pretreatment and their effect on biomass structure Different processes to enhance enzyme production to ameliorate the process of the biorefinery